A Study of Student Learning Attitude Towards E-Learning In The Pandemic Era - Amalia, Direstu; Nugraha, Wildan (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2021)
This study aims to examine student learning attitudes towards e-learning as a learning medium in the pandemic era. This research begins with a survey as input for a quantitative approach. The collected data was then analysed and checked for validation using Pearson's correlation. The results showed that students were ready for class changes from face-to-face to e-learning and considered that e-learning was better in terms of presenting materials and assignments. 82% of students consider Online learning ensures the effectiveness for presenting the work in class. 62% of them respond to adjustments and mastery of technology and applications on computers and the internet can be handled properly so that it can be said that students have good digital competence. However, 50% of students still prefer face-to-face classes to virtual classes because they think face-to-face classes are better in interacting with teachers and friends.